JURIDICAL ANALYSIS OF THE ROLE AND FUNCTION OF CUSTOMS TO PREVENT THE Smuggling of Goods to Realize INCREASING STATE INCOME: STUDY ON TYPE B Customs and Excise Commission in BATAM - Gunawan, Rendi; Fadjriani, Lia; Milanie, Feby (RADJA PUBLIKA, 2021)
In the Juridical Analysis of the Role of Customs and Excise in Supervising and Preventing Crimes of Smuggling of Goods at the Customs Commission Type B Batam, it aims to discuss the legal arrangements for the role of customs in supervising and preventing criminal acts of smuggling of goods and the implementation of obstacle factors, obstacles and solutions for the role of customs in supervising and preventing the crime of smuggling of goods (research study at the Customs and Excise KPU type B Batam). This study aims to determine the Juridical Analysis of the Role of Customs and Excise in Supervising and Preventing the Crime of Smuggling of Goods at the Customs Commission Type B Batam.The research conducted is descriptive research with the method normative legal approach (normative juridical) is carried out by means of study literature. Data collection tools used in this research are data in the form of document studies and literature searches and by using additional data in the form of interviews.The results of the study indicate that the general legal arrangement of Customs and Excise authority according to Law No. 17 of 2006 is, Customs and Excise receives reports or information from someone about a criminal act, summons people to be heard and examined as suspects or witnesses, examines, seeks , and collect information on criminal acts, arrest and detain people suspected of committing criminal acts, request information and evidence from suspects who commit criminal acts.For this reason, it is hoped that with the existence of complete legal rules and firm witnesses related to the crime of smuggling of goods, all related elements are able to understand the legal rules made to protect the public from the threat of danger, and legal rules should be emphasized so that no more criminal acts of smuggling of goods occur.